Pengaruh keunggulan bersaing terhadap kinerja pemasaran pengrajin rotan Pekanbaru - Nofrizal Nofrizal; Aznuryandi Aznuryandi; Arizal N; Azhar Affandi; Undang Juju (Journal of Business & Banking, 2020)
This study attepts to determine the effect of competitive advantage on the marketing performance of rattan craftsmen SMEs where—before the Covid 19 epidemic until the current implementation of New Normal— marketing performance continued to decline and was difficult to develop. Therefore, this benefited to help the SME craftsmen of rattan find and implement factors that can improve marketing performance so that the conditions of the SME Craftsmen continue to develop. This study used a survey method with the sample of 40 respondents of rattan craftsmen in Pekanbaru City. The data were colected using questionnaires and observation techniques, and the data were both primary data and secondary data. The stages of data analysis are validity test, reliability test, classical assumption test, multiple linear regression, t test, f test and determinant coefficient test (R2). The results showed that product uniqueness, product quality and competitive prices had an effect on marketing performance. Simultaneously to the effect of competitive advantage on the marketing performance of UKM Rattan Craftsmen Pekanbaru. It suggest that further study add the variables/factors that can be used to improve marketing performance for MSMEs in Indonesia, especially in Pekanbaru.